Pembelajaran Matematika Interaktif Melalui Permainan Edukatif Seblak Prasmanan Bagi Siswa Kelas V SD Negeri 170924 - Maulidina Panjaitan; Dessy Wulandari; Rahmayani Rahmayani; Eka Khairani Hasibuan Arrifa; Halimah Sari Lubis (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Mathematics learning is often perceived as difficult and monotonous by elementary school students, especially when dealing with abstract concepts such as integers. This community service activity aims to provide a more enjoyable and meaningful learning experience through an educational game themed Seblak Prasmanan Matematika for fifth-grade students of SD Negeri 170924. The method employed is participatory, in which students are directly involved in the learning process through interactive activities such as the “Pak Polisi” game, the introduction of integer concepts, and the main game that connects arithmetic operations with the activity of selecting seblak ingredients representing positive and negative values. The results of the activity indicate an increase in students’ enthusiasm and participation during the learning process, as well as an improvement in their understanding of addition and subtraction of integers. Through this game-based approach, mathematics is no longer viewed as a rigid subject, but as a learning activity closely related to everyday life. This activity also shows that game-based learning can increase students' motivation and creativity in understanding mathematical concepts.